View of the Jangha (wall) of the subsidiary shrine of the Someshwar Mahadev temple - Temples of India Project Team (Jio Institute, 2024)
This is a closer view of the jangha (wall) of the subsidiary shrine in the northwestern corner of the Someshwar Mahadev temple complex. The wall of the pancharatha (with five vertical projections on each side) shrine is very ornate. The central bhadra (central projection) that faces west has a depiction of the Trivikrama form of Vishnu. The other projections have depictions of dancers, apsaras (celestial damsels), and dikpalas (deities for cardinal directions). The inclination of Vishnu imagery on the exterior wall indicates that the shrine must have been dedicated to Vishnu.